2018
DOI: 10.1016/j.ajhg.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in UNC45A Cause a Syndrome Associating Cholestasis, Diarrhea, Impaired Hearing, and Bone Fragility

Abstract: Despite the rapid discovery of genes for rare genetic disorders, we continue to encounter individuals presenting with syndromic manifestations. Here, we have studied four affected people in three families presenting with cholestasis, congenital diarrhea, impaired hearing, and bone fragility. Whole-exome sequencing of all affected individuals and their parents identified biallelic mutations in Unc-45 Myosin Chaperone A (UNC45A) as a likely driver for this disorder. Subsequent in vitro and in vivo functional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 34 publications
2
59
0
1
Order By: Relevance
“…Cochlear hair cells express both UNC45A and UNC45B ( https://umgear.org ), and we hypothesize that either one of these chaperones is required for the correct folding of MYO15 in vivo . Intriguingly, loss-of-function mutations in UNC45A are associated with a human form of syndromic deafness ( 56 ), although it is unknown whether this is caused by defective hair cell stereocilia formation, similar to the phenotype caused by pathogenic Myo15 variants in mouse ( 3 , 5 ). Why might hair cells express both UNC45 paralogs?…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear hair cells express both UNC45A and UNC45B ( https://umgear.org ), and we hypothesize that either one of these chaperones is required for the correct folding of MYO15 in vivo . Intriguingly, loss-of-function mutations in UNC45A are associated with a human form of syndromic deafness ( 56 ), although it is unknown whether this is caused by defective hair cell stereocilia formation, similar to the phenotype caused by pathogenic Myo15 variants in mouse ( 3 , 5 ). Why might hair cells express both UNC45 paralogs?…”
Section: Discussionmentioning
confidence: 99%
“…This protein contributes to tumorigenesis by regulating cancer cell proliferation [ 38 ]. In addition, biallelic loss-of-function mutations in this gene cause the development of osteo-oto-hepato-enteric syndrome, which includes the clinical features of cholestasis, congenital diarrhea, impaired hearing, and bone fragility [ 39 ]. Therefore, the protein encoded by UNC45A may have important physiological functions in several organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found that UNC-45A is abundantly expressed in both the ciliated columnar epithelium of the fallopian tube and the cilia of the ependymocytes. Interestingly, congenital loss-of-function mutations in UNC-45A cause a syndrome characterized by diarrhea, cholestasis, bone fragility, and impaired hearing [ 56 ], all of which symptoms involve organs where cilia play important roles in physiology [ 57 , 58 , 59 ]. Furthermore, almost all of the subjects affected by congenital UNC-45A loss have signs of intellectual disability [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, congenital loss-of-function mutations in UNC-45A cause a syndrome characterized by diarrhea, cholestasis, bone fragility, and impaired hearing [ 56 ], all of which symptoms involve organs where cilia play important roles in physiology [ 57 , 58 , 59 ]. Furthermore, almost all of the subjects affected by congenital UNC-45A loss have signs of intellectual disability [ 56 ]. Although this may be partially due to deafness or/and other aspecific and indirect causes associated with the syndrome, it is also possible that UNC-45A loss may be directly responsible for the intellectual disability of these patients given its wide expression in the central nervous system and its requirement for the extension of neurites [ 29 ].…”
Section: Discussionmentioning
confidence: 99%